Extension of Goosander Mergus merganser distribution into the Carpathian Mountain range - Kajtoch, Åukasz; Bobrek, RafaÅ‚ (Wildfowl, 2014)
The Goosander Mergus merganser occurs mainly in the Holoarctic boreal zone but isolated populations also exist in the Alps, the Balkans and in central Asia. In the late 20th century, the breeding distribution extended to the Carpathian Basin in central Europe, and the species is now widespread in the west of the Carpathian Mountain range, whilst remaining scarce in the east Carpathians and breeding only occasionally in the southern Carpathians. It was estimated that at least 240–360 pairs bred in the Carpathian Mountains in 2010–2013 (of which c. 80% were in Poland), where they are restricted to river valley systems which are generally in a natural or semi-natural state. This remains a rare species in central Europe, meriting conservation measures in the Carpathians and monitoring of its continued expansion in the region.